2017
DOI: 10.1017/s0007114517001805
|View full text |Cite
|
Sign up to set email alerts
|

Dietary polyphenol intake and risk of type 2 diabetes in the Polish arm of the Health, Alcohol and Psychosocial factors in Eastern Europe (HAPIEE) study

Abstract: This study aimed to test the association between dietary content of total and individual classes of polyphenols and incident cases of type 2 diabetes in Polish adults participating to the Health, Alcohol and Psychosocial factors In Eastern Europe study. At baseline, diet by 148-item FFQ and health information were collected from 5806 participants free of diabetes. Self-reported incident type 2 diabetes was ascertained at 2–4-year follow-up visit. OR and 95 % CI of type 2 diabetes comparing the various categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 53 publications
3
48
1
5
Order By: Relevance
“…Buah apel memiliki berbagai macam varietas antara lain apel Anna, Romebauty, Manalagi dan lainnya.Buah apel manalagi memiliki rasa yang lebih manis dibandingkan varietas yang lain. 5,23,24,25 Apel mengandung pektin kimia berserat alami yang mampu mengurangi kadar glukosa darah hingga 50%.Hasil studi yang telah dilakukan di salah satu Universitas di Jepang, menunjukkan bahwa kadar glukosa darah turun secara signifikan pada penderita diabetes mellitus dalam waktu 24 jam setelah makan apel dosis 2 x 100 gram. Selain itu, gejala komplikasi diabetes mellitus juga berkurang secara signifikan dengan mengkonsumsi buah apel.…”
Section: Perbedaan Selisih Perubahan ( δ ) Kadar Glukosa Darah Puasa unclassified
“…Buah apel memiliki berbagai macam varietas antara lain apel Anna, Romebauty, Manalagi dan lainnya.Buah apel manalagi memiliki rasa yang lebih manis dibandingkan varietas yang lain. 5,23,24,25 Apel mengandung pektin kimia berserat alami yang mampu mengurangi kadar glukosa darah hingga 50%.Hasil studi yang telah dilakukan di salah satu Universitas di Jepang, menunjukkan bahwa kadar glukosa darah turun secara signifikan pada penderita diabetes mellitus dalam waktu 24 jam setelah makan apel dosis 2 x 100 gram. Selain itu, gejala komplikasi diabetes mellitus juga berkurang secara signifikan dengan mengkonsumsi buah apel.…”
Section: Perbedaan Selisih Perubahan ( δ ) Kadar Glukosa Darah Puasa unclassified
“…19 Hydroxycinnamic acids include cinnamic, p-coumaric, ferulic, rosmarinic, caffeic and chlorogenic acid. 20 There is epidemiological evidence that phenolic acid intake is inversely associated with occurrence of diabetes, 21 hypertension 22,23 and the metabolic syndrome. 24 Furthermore, preclinical data in experimental models have shown that even a single phenolic acid may exert protective effects against NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…They are the most abundant antioxidants in the diet of human beings 40 . Dietary polyphenol is associated with lower rates of diabetes and cardiovascular disease 41,42 . Phenolic compounds have strong in-vitro and in-vivo antioxidant activities associated with their ability to scavenge free radicals, break radical chain reactions and chelate metals ions 43 .…”
Section: Discussionmentioning
confidence: 99%